Genetic interactions in the spontaneous production of endogenous murine leukemia virus in low leukemic mouse strains (The Rockefeller University Press, 1982)
The spontaneous expression of ecotropic murine leukemia virus (MuLV) in spleen cells of BALB/c, C57BL/6 (B6), and derivative mice was examined as a function of age. The patterns of spontaneous virus induction in vivo correlate with the patterns of virus induction in vitro, which result from the action of two loci, Inc-l and Inb-l (7). Whereas mice carrying Inc-l or Inb-l have similar phenotypes in vitro, they have significantly different phenotypes in vivo. Mice of the Inb-l+/+ genotype, e.g., B6, rarely expressed MuLV, and the titer of MuLV recovered from rare MuLV-positive mice of this genotype was usually low. Mice of the Inc-l+/+ genotype, e.g., BALB/c, expressed low amounts of MuLV early in life, however, from 6-12 mo of age approximately one- half of the Inc-l+/+ mice expressed virus, frequently of high titer. Equal numbers of N-tropic and B-tropic MuLV were recovered from Inb-l+ mice, but predominantly N-tropic MuLV was recovered from Inc-l+ mice. Strains that carry dominant (+) alleles at both Inc-l and Inb-l show higher titers of MuLV earlier in life than strains that carry only Inc- l or Inb-l. The presence of dominant alleles at both loci results in the appearance of predominantly N-tropic virus early in life. These results demonstrate that the principal determinants of spontaneous virus expression in these low leukemic strains of mice are the In loci or genes linked to them. A further inference that can be drawn from these studies is that the appearance of B-tropic virus is by no means a random process but rather results from predictable patterns of MuLV expression and alteration.